Diseño de un manual de políticas y procedimientos de control interno para inventarios de la empresa comercial Ferri Aserrío Solano en la ciudad de Zaruma - Asanza Ochoa, Yessica Nataly (2023)
The degree work has been developed based on the premise that all companies should have adequate control and treatment of inventory. The company in question does not have a control system that allows its employees to know what activities they should be carrying out in the process of receiving, storing, and distributing merchandise. Therefore, it is forced to make emergency decisions that may have consequences such as loss of profitability. The objective of this work is to design a manual of internal control policies and procedures for inventories of the commercial company Ferri Aserrío Solano of the city of Zaruma to improve the control and treatment of the inventory item; where the processes that allow to carry out a correct command of this main item will be detailed, having a manual of policies and internal control procedures for inventories in the company, means that the workers will have a helpful and easy to understand tool to comply with the activities they carry out daily, to guarantee the efficiency of these rules, the administration has to ensure that they are efficiently complied with the approaches chosen within this work were deductive and inductive since these allow us to obtain logical truths based on the facts found once the investigation has been carried out, also comparing it with results that have found in similar investigations carried out previously in this manual of policies and procedures seeks to eliminate the shortcomings of the company based on the principle of good administration in the inventory area, designing a system of organization and respect among all collaborators so that it can meet its objectives. Keywords: Internal control, inventory treatment, merchandise distribution, company inventory.